1993
DOI: 10.1007/bf00980685
|View full text |Cite
|
Sign up to set email alerts
|

Interactions amongHeliothis virescens larvae, cotton condensed tannin and the CryIA(c) ?-endotoxin ofBacillus thuringiensis

Abstract: The potential interactions among a plant-produced allelochemical, a phytophagous insect, and an endotoxin produced byBacillus thuringiensis were investigated using purified cotton condensed tannins, the CryIA(c)δ-endotoxin fromB. thuringiensis subsp.kurstaki strain HD-73, and larvae ofHeliothis virescens. Purified condensed tannin from cotton fed to neonateH. virescens reduced feeding and mortality caused by insecticidal crystals ofB. thuringiensis. In fifth instars, tannin reduced relative growth rate (RGR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…The cause of the increased survival is not known, but the plants could be producing less toxin in young leaves produced by mature plants, or the toxin could become biologically unavailable through sequestration by plant compounds in mature plants. For example, Navon et al (1993) found that tannins purified from cotton plants antagonized the effects of Bt toxins fed to Heliothis virescens larvae and tannin levels are known to increase in field-grown cotton as plants mature (G. P. Fitt, personal communication). Tabashnik (1990) has argued that strategies that attempt to overwhelm the pest's evolutionary responses, such as using high doses of insecticide or combinations of insecticides, are very high-risk strategies because a successful outcome relies on very special conditions to be met.…”
Section: Attenuation In Expression Of Bt Toxins In Plantsmentioning
confidence: 96%
See 1 more Smart Citation
“…The cause of the increased survival is not known, but the plants could be producing less toxin in young leaves produced by mature plants, or the toxin could become biologically unavailable through sequestration by plant compounds in mature plants. For example, Navon et al (1993) found that tannins purified from cotton plants antagonized the effects of Bt toxins fed to Heliothis virescens larvae and tannin levels are known to increase in field-grown cotton as plants mature (G. P. Fitt, personal communication). Tabashnik (1990) has argued that strategies that attempt to overwhelm the pest's evolutionary responses, such as using high doses of insecticide or combinations of insecticides, are very high-risk strategies because a successful outcome relies on very special conditions to be met.…”
Section: Attenuation In Expression Of Bt Toxins In Plantsmentioning
confidence: 96%
“…Additional benefits will accrue to the resistance management of Bt plants because ecological studies will help to identify critical insect-plant interactions such as the feeding patterns of the insect or inter-plant movement-characteristics that determine whether or not tissue or temporal specific expression of Bt in the plants will have a place in resistance management (Gould, 1988a;Roush, 1994). They will help to determine if there are interactions between natural host plant resistance and Bt toxins (Navon et al, 1993) or if expression of Bt is attenuated in transgenic plants grown under field conditions (see below). This information is needed so that we can predict if selection pressure will vary spatially or temporally.…”
Section: Ecology and Resistance Managementmentioning
confidence: 99%
“…27 (Berenbaum, 1988;Castro et al, 2009Castro et al, , 2008Navon et al, 1993). The different host plants to…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…Insect herbivores that ingest high amounts of tannins fail to gain weight and may eventually die. The pigmented cotton, which is also less prone to bollworms attack, also possesses significantly high levels of condensed tannins that disrupt feeding and growth of chewing insects like Helicoverpa, Heliothis, and other similar species (Klocke and Chan, 1982;Smith et al, 1992;Navon et al, 1993;Wu and Guo, 2001), and sap-sucking species (Liu and Yang, 1991;Zhang and Liu, 2003;Ma et al, 2005). In addition, Wang (1997) reported that there were significant inhibitions caused non-interactionally by tannic acid and gossypol, in which the inhibition of the former was stronger than that of the latter, on the growth of cotton bollworm larvae.…”
Section: Tannin and Flavonoidsmentioning
confidence: 96%
“…More than 10000 types of secondary metabolites have been identified in higher plants, and the majority of those whose function has been identified are alkaloids (such as caffeine and nicotine), terpenoids (terpene and pinene), and polyphenols (tannin and flavonoid) (Navon et al, 1993;Ayres et al 1997). Thousands of secondary metabolites have been identified in plants, and many have clearly demonstrated defensive functions (Swain, 1977;Zummo et al, 1984;Gatehouse, 2002).…”
Section: Introductionmentioning
confidence: 99%